2011
DOI: 10.1021/jp109437b
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Disorder in Ti1−xFeyO2−d Nanocrystal Rutile-Based Flowerlike Aggregates: Detection of Anatase

Abstract: Here we report results of systematic investigation of heterogeneity and disorder in Ti 1-x Fe y O 2-d nanorod rutilebased flowerlike aggregates. It was found that Ti 1-x Fe y O 2-d aggregates are composed of two crystalline phases: rutile as a dominant and anatase as a minor phase. Flowerlike aggregates were found to grow from an isometric core ca. 5-10 nm in diameter that was built from anatase and rutile nanorods ca. 5 Â 100 nm that were grown on the anatase surface having base plane (001) intergrowth with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…The shift and broadening of the Raman peaks observed in this study suggest the presence of size effects and can be attributed to the phonon confinement and gross structural disorder with presence of strain in the as‐grown nanocrystalline phase. Similar effect was also observed for the anatase TiO 2 nanoclusters with positive dispersion in the phonon dispersion curve and its line shape for the E g mode . No other peaks corresponding to rutile or any other TiO 2 polymorphs are seen in the spectra, in good agreement with XRD results.…”
Section: Resultssupporting
confidence: 86%
“…The shift and broadening of the Raman peaks observed in this study suggest the presence of size effects and can be attributed to the phonon confinement and gross structural disorder with presence of strain in the as‐grown nanocrystalline phase. Similar effect was also observed for the anatase TiO 2 nanoclusters with positive dispersion in the phonon dispersion curve and its line shape for the E g mode . No other peaks corresponding to rutile or any other TiO 2 polymorphs are seen in the spectra, in good agreement with XRD results.…”
Section: Resultssupporting
confidence: 86%
“…Notably, some authors (Mazza et al, 2007) have reported that the PCM is not an adequate method for explaining the features of the lattice dynamics in rutile nanocrystals. However, satisfactory PCM fits of the Raman spectra of the rutile phase have been obtained here, and the results are presented and compared with previous Raman, HRTEM and XRPD results (Kremenović et al, 2011). The most intense anatase and rutile E g modes were modeled by the PCM in order to estimate the dimensions of the anatase nanoparticles, as well as the diameters of the rutile nanorods.…”
Section: Resultsmentioning
confidence: 60%
“…However, they are systematically different from values obtained by the Thompson-Cox-Hastings pseudo-Voigt function (TCH-pV) parameter method (e.g. in pure TiO 2 the size and strain are 10 nm and 2 Â 10 À3 , respectively), especially for the crystallite size (Kremenović et al, 2011). The crystallite sizes obtained in the [110] direction by the WA and SIB methods are almost three times smaller than the average values (over all directions) obtained from the TCH-pV parameter method, while the RMSS values are about the same.…”
Section: Figurementioning
confidence: 57%
See 1 more Smart Citation
“…However, this scattering peak exhibits a slight shift to the high frequency for the metal modified TiO 2 (Fig. 3a), the shifts from 144 cm −1 for pure TiO 2 to 150 cm −1 for Fe-Ni/Ag/TiO 2 is observed, this results from the defect effects and surface interaction between metal and TiO 2 [41,45,46]. In addition, other four vibration peaks at 398, 514, 639 cm −1 and a weak shoulder at 196 cm −1 are corresponded to B 1g(1) , A 1g ,+B 1g(2) , E g (2) and E g (3) for all samples in Fig.…”
Section: Photocatalytic Reaction Testsmentioning
confidence: 95%